Coronavirus Disease (COVID) -19 Vaccinations and Indonesian Capital Market - R Juwita; F Rosyana; E Purwaningrum (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to compare the Indonesian capital market responses in term of abnormal return, cumulative abnormal return, and trading volume activity due to Coronavirus disease (COVID)-19 Vaccinations. The event study method is used in this research to study Indonesia’s capital market response during the event period. The event period is divided into 2, i.e. 10 days before and after the event and also 30 days before and after the event. The sample was selected by using the purposive sampling method and obtained from 10 pharmaceutical sub-sector companies listed on IDX. The secondary data used in this study are daily data of closing price for each stock, closing price JCI (IHSG), stock volume trading, and outstanding share. The market model is used to predict expected returns. The results found that there were differences in abnormal returns before and after the implementation of the first COVID-19 vaccination in Indonesia. However, there was no difference between cumulative abnormal returns before and after the event. In 10 days before and after the event, there was no difference in trading volume activity. The opposite result was obtained from the 30 days, there were differences between trading volume activity before and after the event.